(untitled) (The International Journal for Scientific Research, 2024)
Background: Birth defect is widely used as a term for congenital anomalies which include the craniofacial defects in newborns. The annual prevalence of infants born with cleft lip (CL) with or without or cleft palate (CP) is 10 in 10,000. Children with cleft lip and palate may have serious complications that affect their development; therefore, this study was designed to determine the overall prevalence of cleft palate, lip, and cleft palate through retrospective study. Methods: The aim of this study to conduct a retrospective record-based research that covers the west area of Libya. We included all the valid complete live birth records, from the Zawia Medical Center (ZMC), in the period covering 2016 to April 2022 using medical records of 17299 patients with CL/CP. Data regarding cleft type, sex, blood group, neonatal body weights, pregnancy periods, age of their mothers and associated syndromes were collected and analyzed. Results: The data utilized in this study were obtained from the birth data registry at the ZMC covering the period between January 2016 and December 2022, the total number of documented orofacial cleft cases with a rate of 0.87/1000 per 1000 live births with mild male gender predominance (53.3%). In contrast with Cleft palate (CP) which have a higher prevalence in female babies. Our results indicated that preterm infants who are having low birth weight (46.7%) and blood group O+ (40%) are more commonly affected, and separately the babies born by mothers with older age have an increased risk of combined CL/CP anomalies (3 out of 17). Some perinatal babies with cleft lip and palate tended to have other defects and /or syndromes (4 out of 17) especially peirrie Robin Syndrome (50%). Conclusion: Due to the high prevalence of oral clefts such as cleft palate, cleft lip, and cleft lip and palate; health system needs to take precautionary measures to reduce the number of patients through their actions on the modifiable and preventable factors, as well as diagnostic and therapeutic measures to reduce its consequences in such children.